Arsenic speciation in shellfish from South China Sea: Levels, estimated daily intake and health risk assessment. (May 2022) - Liu, Shan; Xiao, Qinru; Wang, Fu; Zhong, Shihua; Chen, Yining; Guo, Yichen; Su, Kai; Huang, Min; Chen, Xin; Zhu, Zhou; Lu, Shaoyou
Abstract: The purposes of this study were to measure the concentrations of arsenic speciation in shellfish from South China Sea and evaluate the health risk by local residents through shellfish consumption. The median concentrations (in wet weight) of arsenic speciation in shellfish samples were in the following order: AsB (16.0 mg·kg −1 ) > DMA (1.30 mg·kg −1 ) > AsV (0.23 mg·kg −1 ) > AsC (0.08 mg·kg −1 ) > AsIII (0.05 mg·kg −1 ) > MMA (0.01 mg·kg −1 ). Among shellfish species, Mactra mera and Babylonia areolata were found to accumulate iAs and AsB, respectively. The target hazard quotient values of iAs (THQiAs ) in all shellfish samples were lower than 1. However, the carcinogenic risk values of iAs (CRiAs ) in the Mactra mera, Mytilus galloprovincialis and Pinctada margaritifera were beyond the acceptable range, implying that continuous exposure to iAs pollution via the consumption of these shellfish would pose a potential cancer risk to local consumers. Graphical abstract: Unlabelled Image Highlights: The major species of arsenic in shellfish was non-toxic organic arsenic AsB. Mactra mera and Babylonia areolata accumulated inorganic arsenic and the AsB, respectively. Consumption of Mactra mera, Mytilus galloprovincialis and Pinctada margaritifera poses risk to residents.